2014
DOI: 10.13080/z-a.2014.101.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low precipitation periods on the herbage yield of mesic semi-natural grasslands under different cutting regimes

Abstract: Climatic changes have led to extreme weather events, with longer dry periods affecting forage production in mesic grasslands. The effects of grassland management and years with periods of low precipitation on herbage dry matter (DM) yield were studied in two-long term grassland experiments with different cutting and fertilization regimes for the period 2000-2012. In both experiments, the annual herbage DM yields had high correlations with the amount of precipitation. The correlation was stronger in frequent cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…From Table 4 it is evident that the exceptionally dry year 2007 had an influence also on the botanical composition (significantly higher proposition of grasses to the detriment of forbs), which is in line with Valkó et al (2012). As published by Kramberger et al (2014), the amount of annual herbage DM yield correlated highly with the amount of precipitation during the March-August period. This finding is mentioned and described in relation to climatic conditions also in the paper of Criste et al (2013).…”
Section: Dry Matter Yieldsupporting
confidence: 63%
“…From Table 4 it is evident that the exceptionally dry year 2007 had an influence also on the botanical composition (significantly higher proposition of grasses to the detriment of forbs), which is in line with Valkó et al (2012). As published by Kramberger et al (2014), the amount of annual herbage DM yield correlated highly with the amount of precipitation during the March-August period. This finding is mentioned and described in relation to climatic conditions also in the paper of Criste et al (2013).…”
Section: Dry Matter Yieldsupporting
confidence: 63%
“…From Table 4 it is clear that the exceptionally dry year 2007 also had an effect on the floristic composition (significantly higher proposition of grasses to the detriment of forbs), which is in line with [31]. [32] found that the quantity of annual herbage DM yield correlated highly with the amount of precipitation during the March-August period. This finding is also described in relation to climatic conditions by [33].…”
Section: Dry Matter Yieldssupporting
confidence: 59%